Intravascular imaging of angioplasty balloon under-expansion during pre-dilation predicts hyperelastic behavior of coronary artery lesions - Ghorbannia, Arash; LaDisa, John F. (Frontiers in Bioengineering and Biotechnology, 2023)
Background: Stent-induced mechanical stimuli cause pathophysiological responses in the coronary artery post treatment. These stimuli can be minimized through choice of stent, size, and deployment strategy. However, the lack of real-time target lesion material characterization is a critical barrier to further personalizing treatment. Aims: A new angioplasty technique using integrated optical coherence tomography (OCT) to characterize local stiffness of the target lesion. Methods: After proper institutional oversight, atherosclerotic coronary arteries (n=9) were dissected from human donor hearts for ex vivo material characterization <48 hours post-mortem. Morphology was imaged at the diastolic blood pressure using common intravascular OCT protocols and at subsequent pressures using a specially fabricated perfusion balloon that accommodates the OCT imaging wire. Balloon under-expansion was quantified relative to the nominal balloon size at 8 ATM. Correlation to a constitutive hyperelastic model was empirically investigated (n=13 plaques) using biaxial extension results fit to a mixed Neo-Hookean and Exponential constitutive model. Results: The average circumferential Cauchy stress was 66.5, 130.2, and 300.4 kPa for regions with <15, 15-30, and >30% balloon under-expansion at a 1.15 stretch ratio. Similarly, the average longitudinal Cauchy stress was 68.1, 172.6, and 412.7 kPa, respectively. Consequently, strong Correlation Coefficients >0.89 were observed between balloon under-expansion and stress-like constitutive parameters. These parameters allowed for visualization of stiffness for a range of atherosclerotic plaques. Conclusion: Results suggested balloon under-expansion is a strong predictor of target lesion stiffness. These findings are promising as stent deployment could now be further personalized via patient-specific material characterization of the target lesion obtained pre-operatively.